2014
DOI: 10.1007/s12350-014-9919-z
|View full text |Cite
|
Sign up to set email alerts
|

The utility of ADMIRE-HF risk score in predicting serious arrhythmic events in heart failure patients: Incremental prognostic benefit of cardiac 123I-mIBG scintigraphy

Abstract: 123I-mIBG significantly provides incremental risk stratification for ArE in HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Cardiac 123 I-mIBG imaging is currently indicated for ''scintigraphic assessment of sympathetic innervation of the myocardium in patients with New York Heart Association [NYHA] class II or class III HF and left ventricular ejection fraction [LVEF] B35% … and to help identify patients with lower oneand two-year mortality risks, as indicated by an [HMR] ratio C1.6.'' Nevertheless, much literature suggests a potential broader use, 91 including identification of patients at increased risk of lethal cardiac arrhythmias in the setting of HF, [92][93][94][95] evaluating primary arrhythmic conditions, [96][97][98][99][100] assessing the presence and risk of ischemic heart disease, 101,102 including in situations of hibernating myocardium 103,104 and post-infarction, [105][106][107] evaluating pre-and post-cardiac transplant patients, [108][109][110] identifying diabetic patients at increased risk from cardiac autonomic dysfunction, 111,112 and monitoring toxicity from chemotherapy. 113 However, based on currently available literature, published guidelines, and the FDA package insert, the following indications can be recommended: 114 • For patients with NYHA class II or III heart failure with LVEF B35% to help stratify risk and to promote more informed clinical decision-making when the result of 123 I-mIBG study is likely to influence the decision regarding ICD implant.…”
Section: Tl-201mentioning
confidence: 99%
“…Cardiac 123 I-mIBG imaging is currently indicated for ''scintigraphic assessment of sympathetic innervation of the myocardium in patients with New York Heart Association [NYHA] class II or class III HF and left ventricular ejection fraction [LVEF] B35% … and to help identify patients with lower oneand two-year mortality risks, as indicated by an [HMR] ratio C1.6.'' Nevertheless, much literature suggests a potential broader use, 91 including identification of patients at increased risk of lethal cardiac arrhythmias in the setting of HF, [92][93][94][95] evaluating primary arrhythmic conditions, [96][97][98][99][100] assessing the presence and risk of ischemic heart disease, 101,102 including in situations of hibernating myocardium 103,104 and post-infarction, [105][106][107] evaluating pre-and post-cardiac transplant patients, [108][109][110] identifying diabetic patients at increased risk from cardiac autonomic dysfunction, 111,112 and monitoring toxicity from chemotherapy. 113 However, based on currently available literature, published guidelines, and the FDA package insert, the following indications can be recommended: 114 • For patients with NYHA class II or III heart failure with LVEF B35% to help stratify risk and to promote more informed clinical decision-making when the result of 123 I-mIBG study is likely to influence the decision regarding ICD implant.…”
Section: Tl-201mentioning
confidence: 99%
“…A group of patients who had no ICD discharges (and who, in theory, would not benefit from ICDs) was characterized by both preserved 123 I-MIBG uptake and preserved (more normal) heart rate variability, but this group consisted of only 3 patients. In a recent analysis of the ADMIRE-HF trial program, Al Badarin et al (20) created a risk score for arrhythmic events (the events that would be most directly affected by an ICD) and identified a "low-risk" group of 153 patients in whom only 3 events occurred, for a crude event rate estimate of 2%. The authors acknowledged the absence of external validation but concluded that the data suggested that 123 I-MIBG imaging in such patients could have a ".…”
mentioning
confidence: 99%
“…As pointed out in an accompanying editorial (21), even a risk of 2% may not be low enough to rule out the potential benefit of an ICD. Moreover, authors (such as Al Badarin et al (20)) often focus on point estimates of risk in a studied population. More important is to examine the confidence intervals around the point estimate, as the true risk in the studied population-if it could ever be measured-might be distinctly higher than 2%, especially given the very small number of events (3) in the small population (153 patients) studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal, Al Badarin et al 29 present a re-analysis of ADMIRE-HF trial focusing specifically on the prediction of potentially life-threatening arrhythmic events as defined originally in ADMIRE-HF, in the 778 patients who did not have an ICD at the time of enrollment. Multivariable survival regression was used to determine independent predictors, and derive a predictive risk score The authors found that a HM ratio \1.6 on 123 I-mIBG imaging was associated with a 3.5-fold increase in the likelihood of arrhythmic events [Hazard Ratio (HR) 3.48, 95% CI 1.52-8], independent of other clinical predictors of arrhythmias including left ventricular ejection fraction (LVEF).…”
mentioning
confidence: 99%